اتجاهات الفقر في عدد من البلدان العربية للمدة 1970-2005 - د.داؤد سليمان سلطان; عصمت بكر أحمد (PROSPECTIVE RESEARCHES, 2023)
Developing countries suffer more from the impact of poverty. This paper studies some issues about poverty. Poverty definition is the difference between two concepts absolute and relative poverty. The second aim of this paper is to provide an introduction for the measurement of poverty and try to discuss some of the issues involved. We try to evaluate the impact of antipoverty policies by using some poverty measures in fourth Arab countries Egypt, Yemen, Tunisia, Jordan during the period 1970-2005.